Przegląd badań dotyczących efektywności i produktywności polskiego szkolnictwa wyższego, prowadzonych za pomocą metody DEA i indeksu Malmquista - Brzezicki, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The article reviews the research on Polish higher education conducted for the DEA methods and the Malmquista index. The research was analysed due to various criteria: (1) including DEA models and Malmquist index, (2) areas of activity of higher education institutions, thereafter (3) types, groups and level of higher education analysis, (4) subsequently, the sources of data and variables accepted for the study. The results of the review show that research on Polish higher education is very little diversified, both in terms of the models used and the research area of higher education, with few exceptions.
Keywords: higher education; efficiency; DEA; productivity; Malmquist index; research review